PENGENALAN BUDAYA JEPANG MELALUI PERMAINAN MANNA SUGOROKU BAGI PEMBELAJAR BAHASA JEPANG TINGKAT DASAR - Nana Rahayu (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2018)
Generally, students who enter the Japanese Language Education Study Program Faculty of Teacher Training and Education Riau University have a high interest in Japanese Culture. So that, the introduction of Japanese society and culture is presented in the form of Nihon Jijou subjects in semester 1. For the students or Japanese learners at the basic level, the introduction Japanese culture provides its own motivation in learning Japanese. It is just that their understanding of Japanese culture is only found in the material without feeling directly what Japanese culture is like in everyday Japanese life. One of the Japanese culture introductions is to understand the ways or the attitude of Japanese people when using public transportation, especially trains through the Manna Sugoroku game. To understand this, students are asked to read Japanese letters which is one of the obstacles for students to understand Japanese culture well. Through Manna Sugoroku game students were expected to be able to read the rules using Japanese letter so students independently acquire an introduction to Japanese culture that they have never been known before and students were motivated to learn Japanese by increasing their ability in reading Japanese letter.